Net privacy : how we can be free in an age of surveillance - Molitorisz, Sacha (McGill-Queen's University Press, 2020)
"In our digital world, we are confused by privacy - what is public, what is private? We are also challenged by it, the conditions of privacy so uncertain we become unsure about our rights to it. We may choose to share personal information, but often do so on the assumption that it won't be re-shared, sold, or passed on to other parties without our knowing. In the eighteenth century, philosopher Jeremy Bentham wrote about a new model for a prison called a Panopticon, where inmates surrounded the jailers, always under watch. Have we built ourselves a digital Panopticon? Are we the guards or the prisoners, captive or free? Can we be both? When Kim Kardashian makes the minutiae of her life available online, which is she? With great rigour, this important book draws on a Kantian philosophy of ethics and legal frameworks to examine where we are and to suggest steps - conceptual and practical - to ensure the future is not dystopian. Privacy is one of the defining issues of our time; this lively book explains why this is so, and the ways in which we might protect it."--